The effectiveness of a brief video-based intervention in reducing gender bias in Korea - Bae, Yejin; Jeong, Jisun (Frontiers in Psychology, 2024)
Introduction Gender bias deepens gender disparities by fueling gender conflicts. Thus, effective interventions for gender bias are necessary. Understanding gender discrimination experienced by another gender, both emotionally and logically, may contribute to reducing gender bias in Korean society. Hence, we conducted an online experiment using Video Interventions for Diversity in Science, Technology, Engineering, and Mathematics (VIDS) to examine the effectiveness of shortened VIDS intervention through perspective taking in reducing gender bias. Methods A sample of Korean adults aged 19–39 (n = 160, 61.8% women, 38.2% men) were recruited. In the treatment group, male participants watched VIDS videos that portrayed a woman getting gender prejudiced and female participants watched VIDS videos showing a man receiving gender biased treatment in the society. The videos presented to treatment group consisted of one narrative and one expert video from VIDS, which stimulate emotional and logical understanding of the another gender, respectively. Participants in the control group watched a control video that was irrelevant to gender bias. All participants then answered gender bias questionnaire, as well as cultural orientation questionnaire. Results Cultural orientation as a covariance, ANCOVA (Analysis of Covariance) revealed participants in the treatment group showed significantly lower gender bias than the control group. Within the treatment group, a moderation analysis showed that logical thinking moderated the relationship between emotional immersion and decreased gender bias, meaning stimulated logical thinking from watching the videos affected how engaging emotionally to the another gender’s situation lowers gender bias. Discussion Our findings suggest that VIDS, a video-based gender bias intervention tool, can still be effective when edited briefly. Furthermore, one’s perspective-taking strategy can be considered when trying to decrease gender bias through videos that promote perspective-taking. The findings highlight the possibility of utilizing short video intervention that enhances perspective taking on decreasing gender bias.